Pengaruh Kompensasi Eksekutif, Pertumbuhan Penjualan dan Corporate Social Responsibility Terhadap Penghindaran Pajak - Anisa, Anisa; Pratin, Anjas Mila (JABI (Jurnal Akuntansi Berkelanjutan Indonesia), 2022)
This study aims to examine the effect of executive compensation, sales growth and corporate social responsibility on tax avoidance in primary consumer goods sector companies listed on the Indonesia Stock Exchange in 2017-2021. This type of research is quantitative using secondary data. The total population is 87 companies. Sample selection used purposive sampling techniques and obtained samples of 29 companies. The analysis method used is panel data regression analysis. The results showed that simultaneously executive compensation, sales growth and corporate social responsibility affect tax avoidance. It partially shows that executive compensation and corporate social responsibility have no effect on tax avoidance while sales growth has an effect on tax avoidance.